Relational Model of Teacher Competence, Student Motivation and Learning Facilities on Learning Achievement - Budiyono Pristyadi; Muhammad Syaiful Anam (INNOVATION RESEARCH JOURNAL, 2020)
Education has a very important role in shaping human resources, it is necessary to improve quality inthe world of education. The increase in education lapsed can not be separated from the success of theteaching and learning process. The success of the teaching and learning process can be seen fromstudent achievement. This study aims to determine the effect of teacher competence, studentmotivation, learning facilities on student achievement. The population in this study were final yearstudents in 161 vocational high school students. This study uses a sampling technique that isincidental sampling, the sample used is 100 students, the type of data used is primary data, testing isdone by using multiple linear regression analysis techniques, the results of this study indicate that thevariables of teacher competency, learning motivation, and learning facilities partially affect learningachievement.